Business Process Analysis and Improvement on Training Management in Government Training Institution (Case Study of Institution XYZ) - Kurniawan, Uli Mahendra; Aknuranda, Ismiarta; Kurniawan, Tri Astoto (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
The target indicators for the success of training conducted by the XYZ institution in 2018 are achieved in un-ideal conditions. The target of the average Competency Gap Index (CGI) value is achieved by reducing the measurement parameters of the work competency standard (SKK). This condition is a fact that the success of the training in the XYZ institution still lacks in its achievements. Based on the explanation of the problem, this study will apply the concept of Business Process Management (BPM) to conduct an analysis of the business process of conducting training in the XYZ institution to identify the possible problems that occur in the business process. This study aims to analyze and modeling the current business process of training program (as-is). The research methodology uses literature studies and data collection from interviews, observations, and supporting documents. The results of this study are proposed business processes (to-be) which are recommendations for improvement in current business processes (as-is). The business process is modeled used the standard modeling of Business Process and Notation (BPMN) version 2.0.